PROPHYLACTIC EFFECT OF COENZYME Q10 ON GROSS PARAMETERS OF RAT TESTIS EXPOSED TO MOSQUITO COIL SMOKE INHALATION - Atta, Muhammad Fahad; Qamar, Khadija; Iram, Maria; Safdar, Saba Saleem; Faisal, Tayyaba; Shan, Maryam (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the toxic effect of mosquito coil smoke inhalation on gross parameters of rat testis and explore the protective effect of Coenzyme Q10on testicular toxicity profile. Study Design: Laboratory-based experimental study. Place and Duration of Study: Department of Anatomy Army Medical College, Rawalpindi in collaboration with National Institute of Health, Islamabad, from Jan 2020 to Dec 2020. Methodology: This study was carried out among 30 male Sprague Dawley rats, distributed into three groups as 10 rats/group; group A served as control group, rats in group B were exposed to allethrin-based mosquito coil smoke 4hours/day for 12 weeks. Rats in group C were administered Coenzyme Q10 (10 mg/kg/day) via oral gavage for 12 weeks along with mosquito coil smoke exposure. At the end of study, gross parameters of body weight gain, testicular weight and volume, and relative tissue body weight index of testis were compared among groups. Results: Rats exposed to mosquito coil smoke alone showed significantly less weight gain (p<0.001)), testicular weight (p<0.001), volume (p<0.001), and relative tissue body weight index (p<0.001) as compared to control group. Rats administered Coenzyme Q10 along with mosquito coil smoke exposure exhibited significantly higher weight gain (p<0.001), testicular weight (p<0.001), volume (p<0.001) and relative tissue body weight index (p<0.001) as compared to rats exposed to mosquito coil smoke alone. Conclusion: Long-term inhalation of allethrin-based mosquito coil smoke caused testicular atrophy among rats, as evident by reduced testicular weight, volume and relative tissue body weight index. Whereas, prophylactic oral administration of Coenzyme......................